The Relationship Between Protein Consumption and Hemoglobin Levels of Female Students of Universitas Teuku Umar - Laila Apriani Hasanah Harahap; Siti Maisyaroh Fitri Siregar; Itza Mulyani; Suci Eka Putri; Adelina Irmayani Lubis; Meutia Faradhiba; Nasrianti Syam (Universitas Teuku Umar, 2023)
Anemia is a condition of the body where the hemoglobin (Hb) level in the blood is lower than the normal value, resulting in pallor, weakness, fatigue, dizziness, lack of appetite, decreased fitness, decreased work ability, decreased immunity and impaired wound healing. Protein plays a role in the storage and transportation and absorption of iron. Inadequate protein intake can lead to disturbances in iron metabolism which can affect hemoglobin formation, causing anemia. Adolescent girls are one of the groups that are prone to anemia because adolescent girls experience the menstrual cycle every month. In addition, the condition will be even worse if a woman is married and pregnant, because pregnancy requires more iron for the growth and development of the fetus, which has an impact on infant mortality, abnormal births, low birth weight, and maternal mortality. The purpose of this study was to determine the relationship between protein consumption and hemoglobin levels in adolescent girls. This study used a cross-sectional design and was descriptive analytic. The results of this study showed about 52.7% of respondents had insufficient protein consumption and 60% were anemic. There is a relationship between protein consumption patterns and hemaglobin levels with the value of chi-square statistical test results obtained p value <0.05, namely 0.001.